Formulation and Evaluation of Microspheres of Cefdinir - S.Janet Beula; A.Swathi; Sukantha satapathy; Rajaram Das; N.Sruthi; D.Swetha (International Journal of Pharmacy and Analytical Research, 2014)
Microspheres are sub-micron size polymeric drug carrier systems in which the therapeutic agents are loaded in micrometer. These particles consist of core material, which is the drug, and a coating material. Microspheres are considered as a very promising controlled and targeted drug delivery system. The formulation and clinical application of microspheres is based on the physicochemical, pharmacokinetic and pharmacological properties of drugs. Cefdinir is a beta-lactam antibiotic and is mainly bactericidal. Cefdinir inhibits the third and final stage of bacterial cell wall synthesis by preferentially binding to specific penicillin binding proteins, those are located inside the bacterial cell wall. Cefdinir is a third generation anti-biotic used for the treatment of community - acquired pneumonia, acute bacterial otitis media and uncompleted skin and skin structure infections in adult and pediatric patient. Incorporation of Cefdinir in polymeric microspheres can successfully increase the biological half-life and reduce the therapeutic dose of their drug, thereby minimizing the adverse drug reaction. Cefdinir microspheres were formulated by emulsion solvent evaporation method using ethyl cellulose polymer. All the above studies reveal that the microsphere can serve as an ideal drug delivery system for Cefdinir. Further studies can be done on the stability of cefdinir-loaded microspheres and the improvement in therapeutic efficacy due to the targeting effect on to the specific receptor sites.